Humanist Humanist Culture-Based Principal Leadership in Improving Kindergarten Teacher Competency Development - Kristanti, Arin Ike; Haryono, Haryono; Budiyono, Budiyono (Educational Management, 2022)
Research purposesTo find out the leadership abilities of school principals in improving teacher competency development in ABA Notoyudan Kindergarten Yogyakarta, this research is qualitative research using observation, interview, documentation, and field observations. The subjects of this study were teachers and principals at ABA Notoyudan Kindergarten, Yogyakarta. The results of the study show that the leadership role of the school principal is quite good because it has provided guidance, assistance, supervision, and assessment of problems that occur in the school environment. Both related to the technical implementation and development of teaching education in the form of improvement programs and activities. The impact of the leadership of the school principal was that from the start they did not really care about social change, changes in technology and infrastructure by implementing a humanist culture, new changes could be felt, very cooperative, nimble, and caring and nurturing and trying to create an atmosphere and condition for the school to be more attractive, innovative, and humane. With conduciveness and comfort, colleagues feel at home serving at ABA Notoyudan Kindergarten. Internally and externally, teachers and leaders can survive in competitive conditions, although in practice there is much that must be addressed and improved, such as effort, thought and exact costs. But what is more important is the similarity of vision and mission to improve everything. More importantly, the concept at the beginning is underlined and becomes the focus.